Spectral Characteristics of Alaser Dide (Journal of the College of Basic Education, 2023)
In recent years the number and variety of application of laser to military , industrial and medicine have been increasing rapidly . These new promising class of laser source for such applications are the semiconductor or coherent light emitting diodes C - LED's .The development of semiconductor laser structure capable of generating high power C – LED'S in the near infrared region ( NIR ) and visble region ( VIS ) permits and will continue to permit revolutionary changes and important progress in the therapeutical applications of light [ 1 ] .In the following sections , some experiments are set up to determine a threshold current and some physical processes associated with the operation of diode lasers in pluse mode . The plused operation produces several thermal effects and transient effect which can be observed during a single pluse these . These can be correlated with the temperature rise in the diode laser during the pluse . This will be manifested as changes in the spectrum and decrease in the output power .In the practical it is common to use pluse length of 1 – 10 u sec at K and 0.1 – 1 u sec at room temperature [ 2 ] .